Aggregation and negative interactions in low-diversity and unsaturated monogenean (Platyhelminthes) communities in Astyanax aeneus (Teleostei) populations in a neotropical river of Mexico. (April 2019) - Salgado-Maldonado, Guillermo; Mendoza-Franco, Edgar F.; Caspeta-Mandujano, Juan Manuel; Ramírez-Martínez, Carlos
Abstract: We studied monogenean communities of 11 populations of Astyanax aeneus (Günther) separated by small geographical distances along 60 km of the Lacantún river in Chiapas, Mexico, in February and August 2012. We found 12 monogenean taxa. Amongst these, five species specialist for Astyanax were widely distributed regionally, constituting 90% of the total collected monogeneans, with one of these species dominating most component communities. The high similarities in terms of composition between the component communities (SJaccard  > 60%) as well as in terms of the abundance and composition between infracommunities (SBray Curtis > 40%), provide empirical evidence that transmission, both between hosts at the same location and between component communities, is high and effective. No resemblance pattern was detected between locations in terms of their spatial distribution. The composition of these communities was spatially and temporally consistent over the two very different weather periods sampled. These communities were not saturated. Our analysis suggests that the potential richness of the infracommunities is proportional to the number of monogenean species available in the component community. We found aggregation in the populations and between monogenean species. Intraspecific aggregation is density dependent, suggesting that intraspecific competition for space is not a limiting factor for the development of the population. We evaluated the associations for each species pair and detected 77% negative interactions (134/177 associations), suggesting that interspecific competition plays an important role in shaping these communities. The negative correlations of abundance between pairs of species contributes to confirmation of competition. Intraspecific aggregation increased relative to interspecific aggregation with richness in the component community, facilitating coexistence of the species. Our results suggest that these are interactive communities, where monogeneans disperse efficiently from a common source, colonize patches (hosts) together, and compete with other species even at low population densities. Finally, the coexistence of these species is favored by the unpredictable recruitment and aggregated use of fragmented resources. Graphical abstract: Image 1 Highlights: We explore richness and coexistence of monogeneans of a small fish in a large river. Empirical evidence that transmission between hosts/locations is efficient is provided. We provide empirical evidence of unsaturated/low density but interactive communities. Monogeneans show intra and interspecific aggregation both density-dependent. They establish regionally consistent negative interactions repeated between locations.